BEHAVIORAL LEXEMES AND THEIR IMPORTANCE IN SENTIMENTAL ANALYSIS - Rаhimov Hаsаnboy Komiljonovich (Western European Studies, 2024)
This article is dedicated to exploring the importance of sentimental analysis of behavioral lexemes in the Uzbek language. Behavioral lexemes, as words that express a person’ s ethical and emotional qualities, embody positive, negative, and neutral connotations. The article examines the emotional value of these lexemes and explores the thesaurus-based approaches to their classification. Furthermore, it highlights the linguistic relationships that underlie behavioral lexemes for sentimental analysis, emphasizing the practical significance of building synonym and antonym networks. Methods for processing behavioral lexemes to detect emotions in texts, the connotative meanings of words, and their socio-cultural impact are also analyzed. The article serves as a means to delve deeper into the unique semantic features of the Uzbek language and offers new perspectives on the language through sentimental analysis.
Keywords: Sentimental analysis; neutral lexemes; thesaurus